2018
DOI: 10.15537/smj.2018.7.22293
|View full text |Cite
|
Sign up to set email alerts
|

Beliefs, attitudes and barriers associated with the uptake of the seasonal influenza vaccine among patients visiting primary healthcare clinics

Abstract: Objectives:To explore beliefs, attitudes, and barriers associated with uptake of the seasonal influenza vaccine among visitors to primary healthcare clinics.Methods:This was a cross-sectional, self-administered questionnaire-based study of 300 people visiting Family Medicine Centers, King Abdulaziz Medical City, Riyadh, Saudi Arabia, between May 2017 and October 2017.Results:Most respondents reported that they never get vaccinated (63.3%), but most intend to get the vaccination in future. Only 7.7% of responde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
30
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 16 publications
7
30
0
1
Order By: Relevance
“…The most common concern among the contributors in this study regarding the barriers to influenza vaccine was that they want to avoid vaccinations (58.6%), which is relatively close to a previous study conducted in Riyadh city in which 149 out of 207 (72%) participants gave the same reason [ 15 ].…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…The most common concern among the contributors in this study regarding the barriers to influenza vaccine was that they want to avoid vaccinations (58.6%), which is relatively close to a previous study conducted in Riyadh city in which 149 out of 207 (72%) participants gave the same reason [ 15 ].…”
Section: Discussionsupporting
confidence: 70%
“…A study published in 2018 conducted on patients visiting primary health-care clinics showed that one-third of patients thought influenza is a simple disease and there was no need to prevent it or vaccinate against it, half of them thought their chances of getting the disease are low, and a third do not believe the vaccine is effective. Almost half of our study population believes in all three [ 15 ]. In Germany specifically, a study was conducted to evaluate the reason for low vaccine uptake in patients with comorbid illnesses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 The personal choice appears to be one of the main determinants of refusing vaccination; even this concept is found in several studies that underline how the skepticism toward the vaccine, the perception that the disease is not dangerous and the underestimation of the severity of one's own chronic state are deterrents for the influenza vaccination. [13][14][15] Few patients reported the decision of the GP of not to execute vaccination, an evaluation that does not follow national and international guidelines and which puts the patient's health in concrete risk of danger; this event is consistent with general evidence from the literature that report that physicians are more likely to vaccinate chronic patients than healthy ones. 16 Another determinant of non-vaccination would appear to be the chemotherapy treatment, although there is no contraindication to influenza vaccination during chemotherapy if strategies that do not affect the effectiveness of immunization and treatment are applied (e.g.…”
Section: Discussionsupporting
confidence: 66%
“…More evidence is found regarding the compliance of the chronic patients; the literature shows that chronic patients tend to be skeptical about the importance of vaccination and that they underestimate the consequences of the disease, with subsequently low vaccination coverage . [13][14][15]20 All studies agree that a careful and scrupulous information and education of the patient is necessary to increase adherence to vaccination; [13][14][15]20 the hospital setting, that is the setting of our immunization program, seems to be an ideal scenario for the vaccine promotion. The studies that have dealt with the issue of strategies to increase vaccine compliance assure that patients who receive preventive care are more likely to get their influenza shot than those who do not receive; furthermore, the health professionals involved in the care of patients affected by chronic conditions should encourage patients and family members to get immunized to prevent infectious diseases or minimize the risk.…”
Section: Discussionmentioning
confidence: 99%